2022
DOI: 10.3390/ma15196846
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Modified Epoxy Asphalt Bond Coats with Enhanced Bonding Properties

Abstract: The bonding strength of the bond coat plays an important role in the composite action between the wearing surface and the deck plate of the orthotropic steel deck system. Poor bonding results in the delamination of the wearing surface from the deck plate. Graphene oxide (GO) possesses outstanding mechanical and thermal properties, as well as impressive multifunctional groups, which makes it an ideal reinforcement candidate for polymer matrices. In this study, graphene oxide was used to improve the bonding stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Similar to GNPs, other nanofillers, such as GO, MMT and ATT, also extend the allowable construction time of the neat EABC [ 35 , 47 , 48 ]. Table 4 summarizes the time to 5000 mPa·s of GNP-reinforced EABCs at 120 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to GNPs, other nanofillers, such as GO, MMT and ATT, also extend the allowable construction time of the neat EABC [ 35 , 47 , 48 ]. Table 4 summarizes the time to 5000 mPa·s of GNP-reinforced EABCs at 120 °C.…”
Section: Resultsmentioning
confidence: 99%
“…When used as a bonding layer in the OSD system, the epoxy asphalt bond coat (EABC) needs to have high bonding and mechanical strengths. To improve these properties, nanoclays, such as montmorillonite (MMT) and attapulgite (ATT), and GO have been introduced into EABC [ 35 , 36 ]. Although GNPs have been utilized to reinforce both epoxy and asphalt [ 37 , 38 , 39 , 40 , 41 ], as well as epoxy asphalt binders [ 42 , 43 ], less attention has been paid to GNP-reinforced EABCs.…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be mentioned that asphalt- or polymer-modified asphalt in epoxy asphalt or epoxy polymer-modified asphalt rearranges during the formation of phase-separated microstructures [ 31 , 67 , 68 , 69 ]. Figure 10 presents transmission confocal microscopy images of the unmodified asphalt rubber binder and the modified one with 12% WCO.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the bonding strength, especially at 60 C, was enhanced with the incorporation of GO, and the tensile strength and elongation at break of the modified EABCs increased with the GO loading. [22] Based on the above research, GO showed enormous potential on improving the performances of WEA. Nevertheless, it should be noted that CEA's physical and chemical composition is distinct from that of WEA and HEA.…”
Section: Introductionmentioning
confidence: 98%
“…The results showed that the bonding strength, especially at 60 °C, was enhanced with the incorporation of GO, and the tensile strength and elongation at break of the modified EABCs increased with the GO loading. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%